E-Learning Materials Assisted by Augmented Reality in the Subject of Natural Sciences, Circulatory System Material for Grade V Elementary School - Tri Andika Rahman; Novi Setyasto (Postgraduate, University of Mataram, 2025)
Natural and Social Sciences (IPAS) at the elementary school level still faces a number of challenges that affect the achievement of student learning outcomes. This study was conducted using a research and development (R&D) method based on the Borg and Gall model with the aim of developing and testing the feasibility, practicality and effectiveness of e-learning materials assisted by augmented reality (AR). Researchers collected data using test techniques (pretest-posttest) and non-tests in the form of observations, interview results, surveys and document data. The e-learning materials assisted by AR developed by researchers obtained very feasible criteria results from material, media and language validator experts. E-learning materials assisted by AR have proven effective in improving student learning outcomes, as seen from the increase in the average score between the pretest and posttest achieved by students so that a high N-gain score of 0.76 can be obtained. Based on the results of the questionnaire responses given, very positive responses can be obtained from teachers and students. From these results, it can be concluded that AR-based e-teaching materials are declared feasible and practical to use and effective in improving student learning outcomes in the subject of science with the topic of the circulatory system in class V of SD Negeri Ngaliyan 03